2011
DOI: 10.3322/caac.20121
|View full text |Cite
|
Sign up to set email alerts
|

Cancer statistics, 2011

Abstract: Each year, the American Cancer Society estimates the numbers of new cancer cases and deaths expected in the United States in the current year and compiles the most recent data on cancer incidence, mortality, and survival based on incidence data from the National Cancer Institute, the Centers for Disease Control and Prevention, and the North American Association of Central Cancer Registries and mortality data from the National Center for Health Statistics. A total of 1,596,670 new cancer cases and 571,950 death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
1,605
1
17

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 3,685 publications
(1,630 citation statements)
references
References 27 publications
7
1,605
1
17
Order By: Relevance
“…Siegel et al . reported that the lung cancer death rate in men in the US decreased by 2.0% per year from 1994 to 2006 16. In women, although lung cancer death rates continued to increase by 0.3% per year from 1995 to 2005, more recent data show a decline of 0.9% per year from 2003 to 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Siegel et al . reported that the lung cancer death rate in men in the US decreased by 2.0% per year from 1994 to 2006 16. In women, although lung cancer death rates continued to increase by 0.3% per year from 1995 to 2005, more recent data show a decline of 0.9% per year from 2003 to 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Although proportions of patient survival are improving, over half a million people die from cancer each year in the United States alone. Moreover, cancer outranks cardiovascular disease as the number one cause of death in the United States for individuals under the age of 85 3. Screening and prevention efforts can reduce mortality due to cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The American Cancer Society estimates that 1 596 670 new cases of colon cancer (822 300 in men and 774 370 in women) were diagnosed in 2011 (Siegel et al, 2011). Approximately 20% of CRC patients have already present with metastasis disease at the time of their diagnosis, and surgery cannot always extirpate the recurrence of advanced CRC.…”
Section: Introductionmentioning
confidence: 99%